(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Objectives the objective of this study is to compare the root resorption accompanied orthodontic treatment using fixed orthodontic appliance versus removable clear aligner. Material and methods This prospective randomized clinical study was conducted on a sample of 30 patients with mild to moderate crowding. The patient ages ranged from (12-18) years. Patients were randomly divided into three groups; Group Ⅰ: ten patients treated with fixed orthodontic appliance using Roth brackets 0.022-inch slot. Group Ⅱ: ten patients treated with removable clear aligner. Group Ⅲ: ten patients treated with removable clear aligner with application of low-level LASER. Each patient in the study had a pre and post treatment CBCT. Results root resorption was measured by importing pre and post treatment CBCT on Mimics software (version 18, Materialise, Leuven, Belgium) to reconstruct the roots in 3D. conclusion Root resorption accompanied with aligners is considered less than fixed appliances however the difference is not significant. The use of laser has no effect on reducing or minimizing the incidence of root resorption.